Association between Neck Circumference and the Risk of Decreased Estimated Glomerular Filtration Rate in the General Population of China: A Cross-Sectional Study. (24th November 2020) - Xue, Jing; Li, Bing; Wang, Jie; Yu, Songyan; Wang, Anping; An, Ping; Mu, Yiming
Abstract : Background . The burden of chronic kidney disease is increasing substantially worldwide. Neck circumference (NC), an anthropometric index for upper-body adiposity, has been recognized as an indicator of cardiometabolic diseases. However, the association between NC and renal dysfunction has not been fully disclosed. Objectives . The aim of this study was to investigate the association between NC and estimated glomerular filtration rate (eGFR) in the general population in China. Methods . A total of 8805 participants (3322 men and 5483 women) were enrolled in this study. Logistic regression analysis was conducted to examine the association between NC and eGFR. The male and female subjects were divided into four groups according to the NC quartiles. The primary outcome was defined as an eGFR ≤ 90 mL / min / 1.73 m 2 . Results . Logistic regression analysis revealed that in both sexes, higher NC was significantly associated with a higher risk of decreased eGFR even after fully adjusting for age, other anthropometric indexes, traditional risk factors for chronic kidney diseases, and sociologic risk factors (quartile 1 as a reference; the odds ratios [95% confidence intervals] were as follows: quartile 2, 1.26 [0.99-1.59]; quartile 3, 1.40 [1.07-1.83]; and quartile 4, 1.71 [1.22-2.38], in men; quartile 2, 1.14 [0.95-1.37]; quartile 3, 1.31 [1.03-1.66]; and quartile 4, 1.32 [1.04-1.68], in women). Stratified analyses suggested that the association was significant among subjects with prediabetes or normal serum uric acid levels and those without cardiovascular diseases (CVD). Among subjects with CVD, the association persisted only in males. When the subjects were stratified according to blood pressure or BMI, the association persisted among male subjects with abnormal blood pressure and was strengthened among male subjects who were overweight/obese, while the association disappeared among female subjects. Conclusions . NC is independently associated with the risk of decreased eGFR in the general population in China, indicating that NC could contribute to renal dysfunction risk assessment.